A high-toughness polyolefin film and preparation method thereof

By introducing ternary segment structures and appropriate auxiliary materials into the polyolefin film and adopting the melt extrusion tensile process, the problem of insufficient toughness and light transmission of polyolefin films is solved, and a high toughness and light transmission of polyolefin film is achieved, which is suitable for a variety of application scenarios.

CN116656036BActive Publication Date: 2025-04-04浙江大学宁波国际科创中心
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310787825.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2025-04-04
Estimated Expiration
2043-06-29

AI Technical Summary

Technical Problem

The existing polyolefin films have shortcomings in toughening, making them difficult to have both high toughness and high light transmission, and the preparation process is complex, the cost is high, and the film thickness is difficult to control.

Method used

A polyolefin film material composed of the first polymer component and the second polymer component is prepared by a melt extrusion tensile process. The first polymer component contains a ternary chain segment structure, and the auxiliary material components include antioxidants, compatibilizers, crosslinking agents, etc. to improve the toughness and light transmittance of the film.

Benefits of technology

It has achieved a polyolefin film with high toughness and high light transmittance, with significantly improved elongation of break and impact strength of the mark. The film has a high light transmittance and low water vapor transmittance, and is suitable for a variety of battery packaging films and sealing components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116656036B_ABST
    Figure CN116656036B_ABST
Patent Text Reader

Abstract

The present invention discloses a high-toughness polyolefin film and a preparation method thereof. The high-toughness polyolefin film is composed of three parts: a first polymer component, a second polymer component, and an auxiliary material component, wherein the first polymer component is a copolymer of ethylene or propylene and three different α-olefins, and the α-olefin is selected from α-olefins greater than 3 carbon atoms and less than 12 carbon atoms, and the content of the ternary segment structure I composed of three consecutive α-olefin units in the first polymer component is 0.001mol%-3mol%; the three α-olefins are α-olefin A, α-olefin B, and α-olefin C according to the number of carbon atoms from small to large, and the molar ratio of α-olefin A, α-olefin B, and α-olefin C is (0.1-2.5):1:(0.1-4.0). The high-toughness polyolefin film has high light transmittance (>90%) and low water vapor permeability (<5g / m 2 / 24hr) and can be used as encapsulation film for crystalline silicon cells, perovskite cells, and organic thin film cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polyolefin film material and a preparation method thereof, in particular to a high-performance polyolefin film and a preparation method thereof. Background Art

[0002] Patent CN108177401B discloses a polyolefin film, a preparation method thereof and a photosensitive material covering film containing the same. The polyolefin film comprises a first outer layer, an intermediate layer and a second outer layer stacked in sequence, wherein the intermediate layer comprises 60-100wt% of a re-bondable polyolefin and 0-40wt% of a low-density polyethylene. The polyolefin film is blow-molded by a three-layer co-extrusion blow molding machine. The covering film comprises an anti-puncture layer, a light-shielding and moisture-blocking layer and the above-mentioned polyolefin film stacked in sequence. The outer layer and the intermediate layer of the polyolefin film provided by the invention can be repeatedly peeled, layered and pasted and compounded, and the covering film prepared therefrom can be repeatedly pasted after being torn open, thereby avoiding the problem that the traditional covering film loses its function after being opened, and improving the utilization rate of the packaging material. However, this method has a complicated process and requires three extruders to co-extrude a multi-layer polyolefin film, which is costly, and the thickness of the film is difficult to control to a thickness of less than 5μm.

[0003] Patent CN106893183A provides a polyolefin film, the components and weight proportions of which are 65-95 parts of polyolefin resin, 5-25 parts of inorganic filler, 0.1-5 parts of ultraviolet absorber, and 0.1-5 parts of antioxidant, wherein the inorganic filler is composed of 20%-100% filler A and 0-80% filler B, wherein filler A is composed of packaging material and core material. The polyolefin film of the invention has good flame retardancy, high CTI value, and good water vapor barrier property, and is applied to solar cell back panels to improve the flame retardancy and insulation of solar cell back panels. However, the addition of 5-25 parts of inorganic filler not only affects the light transmittance of the film product, but also the compatibility of polyolefin and inorganic filler has always been a difficult problem in material preparation, and the stretchability and toughness of the film will be greatly affected, and it is difficult to prepare a high-toughness polyolefin film.

[0004] Thinning, transparency enhancement and toughening of polyolefin films are the key to improving product added value, economic benefits and product performance. The present invention aims to disclose a formula composition of a high-toughness polyolefin film and a preparation method of the high-toughness polyolefin film, thereby solving this problem. Summary of the invention

[0005] In order to solve the above technical problems, the object of the present invention is to provide a high-toughness polyolefin film and a preparation method thereof, wherein the high-toughness polyolefin film has the characteristics of high toughness and high transparency.

[0006] According to one object of the present invention, the present invention provides a high-toughness polyolefin film, wherein the high-toughness polyolefin film is obtained by melt extrusion and stretching of polyolefin film material pellets composed of a first polymer component, a second polymer component, and an auxiliary material component, wherein, by weight, the content of the first polymer component is 100 parts; the content of the second polymer component is 1-15 parts; by weight, the auxiliary material component includes 0-0.5 parts of an antioxidant, 0-0.5 parts of a compatibilizer, 0.5-2.5 parts of a cross-linking agent, 0-0.2 parts of a co-cross-linking agent, and 0-0.2 parts of an opening agent;

[0007] The first polymer component is a copolymer of ethylene or propylene and three different α-olefins, wherein the α-olefin is selected from α-olefins having more than 3 carbon atoms and less than 12 carbon atoms, and the content of the ternary segment structure I composed of three consecutive α-olefin units in the first polymer component is 0.001 mol%-3 mol%; the three α-olefins are α-olefin A, α-olefin B, and α-olefin C in order of carbon atom number from small to large, and in the first polymer component, the molar ratio of α-olefin A, α-olefin B, and α-olefin C is (0.1-2.5):1:(0.1-4.0);

[0008] The second polymer component is one or more of low-density polyethylene (LDPE), polybutene-1 (PB-1), ethylene-vinyl acetate copolymer (EVA), olefin multi-block copolymer (OBC), ethylene propylene diene monomer rubber (EPDM), thermoplastic elastomer (TPE) or thermoplastic polyurethane elastomer (TPU).

[0009] According to a preferred embodiment of the present invention, the weight average molecular weight of the first polymer component is 3-400 kg / mol, the molecular weight distribution index is 1.1-5.0, the melting temperature is 30-110°C, the tensile strength at break is 1-30 MPa, there is no breakage in the impact test at room temperature and -20°C, and the Shore A hardness is 45-90.

[0010] In the high-toughness polyolefin film provided by the present invention, the combination of three different α-olefins in the first polymer component is 1-butene / 1-pentene / 1-hexene, 1-butene / 1-pentene / 1-heptene, 1-butene / 1-pentene / 1-octene, 1-butene / 1-pentene / 1-nonene, 1-butene / 1-hexene / 1-heptene, 1-butene / 1-hexene / 1-octene, 1-butene / 1-hexene / 1-nonene, 1-butene / 1-heptene / 1-octene, 1-butene / 1-hexene / 1-nonene, 1-butene / 1-heptene / 1-heptene, 1-butene / 1-hexene / 1-octene, 1-butene / 1-hexene / 1-nonene, 1-butene / 1-heptene / 1-heptene. One of octene, 1-butene / 1-heptene / 1-nonene, 1-pentene / 1-hexene / 1-heptene, 1-pentene / 1-hexene / 1-octene, 1-pentene / 1-hexene / 1-nonene, 1-pentene / 1-heptene / 1-octene, 1-pentene / 1-heptene / 1-nonene, 1-pentene / 1-heptene / 1-nonene, 1-pentene / 1-octene / 1-nonene, 1-hexene / 1-heptene / 1-octene, 1-hexene / 1-heptene / 1-nonene, 1-heptene / 1-octene / 1-nonene.

[0011] According to one aspect of the present invention, the molar ratio of α-olefin A, α-olefin B, and α-olefin C in the first polymer component is (0.2-3.0):1:(0.2-3.0), preferably (0.3-2.5):1:(0.3-2.5), and the molar ratio of α-olefin to ethylene or propylene is (0.1-1.0):1.

[0012] According to one aspect of the present invention, the content of the ternary segment structure I composed of three consecutive α-olefin units in the first polymer component (i.e., AAA+AAB+AAC+ABA+ABB+ABC+ACA+ACB+ACC+BAA+BAB+BAC+BBA+BBB+BBC+BCA+BCB+BCC+CAA+CAB+CAC+CBA+CBB+CBC+CCA+CCB+CCC fragment structure) is 0.001 mol%-3 mol%, and the content of the ternary segment structure II composed of two consecutive α-olefin units and one ethylene unit (i.e., EAA+EAB+EAC+EBA+EBB+EBC+ECA+ECB+ECC+AAE+ABE+ACE+BAE+BB The content of the ternary segment structure III composed of two discontinuous α-olefin units and one ethylene unit (i.e., the AEA+AEB+AEC+BEA+BEB+BEC+CEA+CEB+CEC fragment structure) is between 0.01 mol% and 15 mol%, and the content of the ternary segment structure IV composed of three continuous ethylene units (i.e., the EEE fragment structure) is between 50 mol% and 90 mol%.

[0013] In a specific embodiment of the present invention, the first polymer component is prepared by a high temperature solution polymerization process, the temperature of the solution polymerization process is 100-180°C, the pressure is 10-50 bar, the catalyst is selected from one or more of metallocene catalysts, late transition metal catalysts, Ziegler-Natta catalysts, non-metallocene catalysts, and FI catalysts, and the cocatalyst is selected from one or more of methylaluminoxane, modified methylaluminoxane, ethylaluminoxane, butylaluminoxane, trimethylaluminum, triethylaluminum, triisobutylaluminum, trihexylaluminum, trioctylaluminum, monoethylaluminum, dichloroethylaluminum, triphenylborane, tri(4-fluorophenyl)borane, tri(pentafluorophenyl)borane, tri(3,5-difluorophenyl)borane, and tri(2,4,6-trifluorophenyl)borane. In the polymerization, the ratio of the amount of mixed α-olefins (mol) added in A / B / C is (0.1-2.5):1:(0.1-4.0).

[0014] Another object of the present invention is to provide a method for preparing the high-toughness polyolefin film, which comprises: mixing the first polymer component, the second polymer component, and the auxiliary material component in a formula amount by a high-speed mixer at a rotation speed of 100-1000rpm for 10-30min, and then melt-extruding, pelletizing and drying through a twin-screw extruder to obtain high-toughness polyolefin film pellets; the high-toughness polyolefin film pellets are melt-extruded through a single-screw extruder, and stretched at a stretching ratio of 2-20 times to obtain a high-toughness polyolefin film with a thickness of 2-700μm.

[0015] Preferably, the temperature of the twin-screw extruder is 60-230° C., and the rotation speed is 10-200 rpm.

[0016] Preferably, the temperature of the single-screw extruder is 70-200° C., the rotation speed is 10-200 rpm, the stretching ratio is 3-15 times, and the thickness of the high-toughness polyolefin film is 2-600 μm.

[0017] The third object of the present invention is to provide an application of a high-toughness polyolefin film, wherein the high-toughness polyolefin film has high light transmittance (>90%), low water vapor transmission rate (<5g / m 2 / 24hr) and can be used to prepare encapsulation films for crystalline silicon cells, perovskite cells, and organic thin-film cells. It can also be used to prepare sealing components, heavy packaging films, POF films that have high requirements for transmittance and toughness, or for 5G / 6G communication fields.

[0018] The present invention has the following outstanding gain effects: the high-toughness polyolefin film described in the present invention has higher toughness than the current films, which is mainly reflected in high elongation at break and high drop impact strength. It can be more than 50% higher than the elongation at break and 65% higher than the film of the same thickness prepared from polyolefin materials with the same molecular weight and molecular weight distribution. The improvement of the toughness of the polyolefin film is mainly due to the high content of ternary segment structures I, II and III in the first polymer component, especially the formation of ternary segment structure I, and the large number of carbon atoms in the comonomer (that is, the molecular chain branch content in the first polymer component is high and the branch is longer). BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is the NMR carbon spectrum of the first polymer component containing ternary segment structures Ⅰ, Ⅱ, Ⅲ and Ⅳ.

[0020] Figure 2 It is the elongation at break obtained by testing the comparative examples 1-2 and the high-toughness polyolefin films 1-4 respectively according to the specific implementation of the comparative examples 1-2 and the embodiments 1-4.

[0021] Figure 3 According to the specific implementation of Comparative Examples 1-2 and Examples 1-4, the dart drop impact strength is obtained by testing the Comparative Examples 1-2 and the high-toughness polyolefin films 1-4 respectively. DETAILED DESCRIPTION

[0022] The following will be combined with the drawings in the embodiments of the present invention and the comparative examples to clearly and completely describe the technical solutions in the embodiments of the present invention and the comparative examples. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] The following methods were used to test the structure or properties of the polyolefins and films produced in the examples described:

[0024] Nuclear Magnetic Resonance Spectrometer ( 13 C-NMR) was used to test the α-olefin insertion rate of the material.

[0025] The universal testing machine is used to test the elongation at break of materials. The test standard is GB / T 1040.1-2006.

[0026] The dart drop impact strength tester is used to test the dart drop impact strength of materials. The test standard is GB / T9639.1-2008.

[0027] Embodiment 1:

[0028] 1) Purge the polymerization reaction apparatus with high-purity nitrogen to remove moisture and oxygen inside the reaction apparatus. Dissolve 2 μmol of metallocene catalyst in 1 ml of toluene for standby use. Adjust the temperature of the polymerization reactor to 110°C, add 1L of hexane, 450mL of mixed α-olefins, including 80mL of 1-pentene, 120mL of 1-hexene, and 250mL of 1-octene, and then add 1.6mmol of co-catalyst methylaluminoxane and 2μmol of metallocene catalyst in sequence, pass ethylene, ethylene pressure 20bar, polymerize for 20min, and obtain polyolefin copolymer X1 (first polymer component).

[0029] 2) 100 kg of polyolefin copolymer X1, 2 kg of LDPE, 2 kg of LLDPE, 2 kg of EPDM, 0.1 kg of compatibilizer, 1.0 kg of crosslinking agent, 0.1 kg of auxiliary crosslinking agent, 0.1 kg of anti-blocking agent and 0.1 kg of antioxidant were mixed by a high-speed mixer at a speed of 800 rpm for 10 min, and then melt-extruded by a twin-screw extruder at 180° C. and 30 rpm, pelletized and dried to obtain high-toughness polyolefin film pellets. The high-toughness polyolefin film pellets were melt-extruded by a single-screw extruder at 200° C. and 60 rpm, and stretched at a stretch ratio of 12 times to obtain a high-toughness polyolefin film 1 with a thickness of 15±0.31 μm.

[0030] The characterization results of the high-toughness polyolefin film 1 and the polyolefin copolymer X1 are shown in Table 1.

[0031] Embodiment 2:

[0032] 1) Purge the polymerization reaction apparatus with high-purity nitrogen to remove moisture and oxygen inside the reaction apparatus. Dissolve 2 μmol of metallocene catalyst in 1 ml of toluene for standby use. Adjust the temperature of the polymerization reaction kettle to 160°C, add 1L of hexane, 600mL of mixed α-olefins, including 260mL of 1-pentene, 200mL of 1-hexene, and 140mL of 1-nonene, and then add 2mmol of co-catalyst methylaluminoxane and 2μmol of metallocene catalyst in sequence, pass ethylene, ethylene pressure 40bar, polymerize for 30min, and obtain polyolefin copolymer X2 (first polymer component).

[0033] 2) 100 kg of polyolefin copolymer X2, 2 kg of OBC, 2 kg of LLDPE, 2 kg of TPU, 0.1 kg of compatibilizer, 0.6 kg of crosslinking agent, 0.2 kg of auxiliary crosslinking agent, 0.2 kg of anti-blocking agent and 0.2 kg of antioxidant were mixed by a high-speed mixer at a speed of 800 rpm for 15 min, and then melt-extruded by a twin-screw extruder at 180° C. and 30 rpm, pelletized and dried to obtain high-toughness polyolefin film pellets. The high-toughness polyolefin film pellets were melt-extruded by a single-screw extruder at 180° C. and 80 rpm, and stretched at a stretch ratio of 13 times to obtain a high-toughness polyolefin film 2 with a thickness of 15±0.29 μm.

[0034] The characterization results of the high-toughness polyolefin film 2 and the polyolefin copolymer X2 are shown in Table 1.

[0035] Embodiment 3:

[0036] 1) Purge the polymerization reaction apparatus with high-purity nitrogen to remove moisture and oxygen inside the reaction apparatus. Dissolve 2 μmol of non-metallocene catalyst in 1 ml of toluene for standby use. Adjust the temperature of the polymerization reactor to 170°C, add 1L of hexane, 1200mL of mixed α-olefins, including 100mL of 1-hexene, 350mL of 1-heptene, and 750mL of 1-octene, and then add 1.2mmol of co-catalyst methylaluminoxane and 2μmol of non-metallocene catalyst in sequence, pass ethylene, ethylene pressure 50bar, polymerize for 40min, and obtain polyolefin copolymer X3 (first polymer component).

[0037] 2) 100 kg of polyolefin copolymer X3, 6 kg of LLDPE, 0.1 kg of compatibilizer, 1.5 kg of crosslinking agent, 0.1 kg of auxiliary crosslinking agent, 0.1 kg of anti-blocking agent and 0.1 kg of antioxidant were mixed by a high-speed mixer at a speed of 800 rpm for 20 min, and then melt-extruded by a twin-screw extruder at 200° C. and 60 rpm, pelletized and dried to obtain high-toughness polyolefin film pellets. The high-toughness polyolefin film pellets were melt-extruded by a single-screw extruder at 190° C. and 40 rpm, and stretched at a 3-fold stretch ratio to obtain a high-toughness polyolefin film 3 with a thickness of 200±1.01 μm.

[0038] The characterization results of high-toughness polyolefin film 3 and polyolefin copolymer X3 are shown in Table 1.

[0039] Embodiment 4:

[0040] 1) Purge the polymerization reaction apparatus with high-purity nitrogen to remove moisture and oxygen inside the reaction apparatus. Dissolve 2 μmol of non-metallocene catalyst in 1 ml of toluene for standby use. Adjust the temperature of the polymerization reactor to 130°C, add 1L of hexane, 1500mL of mixed α-olefins, including 500mL of 1-pentene, 400mL of 1-hexene, and 300mL of 1-octene, and then add 2mmol of co-catalyst methylaluminoxane and 2μmol of non-metallocene catalyst in sequence, pass ethylene, ethylene pressure 30 bar, polymerize for 20 minutes, and obtain polyolefin copolymer X4 (first polymer component).

[0041] 2) 100 kg of polyolefin copolymer X4, 6 kg of LDPE, 0.1 kg of compatibilizer, 1.4 kg of crosslinking agent, 0.2 kg of auxiliary crosslinking agent, 0.1 kg of anti-blocking agent and 0.2 kg of antioxidant were mixed by a high-speed mixer at a speed of 800 rpm for 25 min, and then melt-extruded by a twin-screw extruder at 170° C. and 50 rpm, pelletized and dried to obtain high-toughness polyolefin film pellets. The high-toughness polyolefin film pellets were melt-extruded by a single-screw extruder at 180° C. and 30 rpm, and stretched at a 3-fold stretch ratio to obtain a high-toughness polyolefin film 4 with a thickness of 200±0.89 μm.

[0042] The characterization results of high-toughness polyolefin film 4 and polyolefin copolymer X4 are shown in Table 1.

[0043] Comparative Example 1:

[0044] 1) Purge the polymerization reaction apparatus with high-purity nitrogen to remove moisture and oxygen inside the reaction apparatus. Dissolve 2 μmol of metallocene catalyst in 1 ml of toluene for standby use. Adjust the temperature of the polymerization reaction kettle to 110° C., add 1 L of hexane, 450 mL of 1-octene, 1.6 mmol of cocatalyst methylaluminoxane, 2 μmol of metallocene catalyst, introduce ethylene, the ethylene pressure is 20 bar, and polymerize for 20 min to obtain a polyolefin copolymer X1'.

[0045] 2) 100 kg of polyolefin copolymer X1', 2 kg of LDPE, 2 kg of LLDPE, 2 kg of EPDM, 0.1 kg of compatibilizer, 0.5 kg of crosslinking agent, 0.1 kg of co-crosslinking agent, 0.1 kg of anti-blocking agent and 0.1 kg of antioxidant were mixed by a high-speed mixer at 800 rpm for 10 min, and then melt-extruded by a twin-screw extruder at 180° C. and 30 rpm, pelletized and dried to obtain polyolefin film pellets. The polyolefin film pellets were melt-extruded by a single-screw extruder at 200° C. and 60 rpm, and stretched at a 12-fold stretch ratio to obtain a polyolefin film 1' with a thickness of 15±0.35 μm.

[0046] The characterization results of the polyolefin film 1' and the polyolefin copolymer X1' are shown in Table 1.

[0047] Comparative Example 2:

[0048] 100 kg of commercially available polyolefin copolymer (brand name Engage 8150), 6 kg of LLDPE, 0.1 kg of compatibilizer, 1.3 kg of crosslinking agent, 0.1 kg of auxiliary crosslinking agent, 0.1 kg of anti-blocking agent and 0.1 kg of antioxidant were mixed by a high-speed mixer at 800 rpm for 20 minutes, and then melt-extruded by a twin-screw extruder at 200° C. and 60 rpm, pelletized and dried to obtain polyolefin film pellets. The polyolefin film pellets were melt-extruded by a single-screw extruder at 190° C. and 40 rpm, and stretched at a 3-fold stretch ratio to obtain a high-toughness polyolefin film 2' with a thickness of 200±1.10 μm.

[0049] The characterization results of the polyolefin film 2' and the commercially available polyolefin copolymer are shown in Table 1.

[0050] Table 1 Comparative Examples 1-2 and Examples 1-4 Film Performance Test and Characterization Results

[0051]

[0052] Figure 1 This is the NMR carbon spectrum of the first polymer component X1 obtained in Example 1, which contains ternary segment structures Ⅰ, Ⅱ, Ⅲ and Ⅳ. Figure 2 It is the elongation at break obtained by testing the comparative examples 1-2 and the high-toughness polyolefin films 1-4 respectively according to the specific implementation of the comparative examples 1-2 and the embodiments 1-4. Figure 3 According to the specific implementation of Comparative Examples 1-2 and Examples 1-4, the dart drop impact strength is obtained by testing the Comparative Examples 1-2 and the high-toughness polyolefin films 1-4 respectively.

[0053] As shown in the above table and the accompanying drawings, the method of the present invention can be used for the preparation of high-toughness polyolefin film. Through the high-toughness polyolefin film formula and preparation process mentioned in the invention, a high-toughness polyolefin film with a breaking elongation of more than 50% and a dart drop impact strength of more than 65% can be obtained. Compared with Comparative Example 1, the comonomer content in the first polymer component of Examples 1 and 2 is similar, while the breaking elongation of polyolefin film 1 and polyolefin film 2 is 72.7% and 130.6% higher than that of polyolefin film 1', respectively, and the dart drop impact strength of polyolefin film 1 and polyolefin film 2 is 160% and 203% higher than that of polyolefin film 1', respectively. Compared with Comparative Example 2, the comonomer content in the first polymer component of Examples 3 and 4 is also similar, while the breaking elongation of polyolefin film 3 and polyolefin film 4 is 165.3% and 199.0% higher than that of polyolefin film 2', respectively, and the dart drop impact strength of polyolefin film 3 and polyolefin film 4 is 111.5% and 124.5% higher than that of polyolefin film 2', respectively. This is mainly because Examples 1-4 contain ternary segment structure I which has a significant effect on toughness enhancement, while Comparative Example 1-2 does not contain ternary segment structure I.

[0054] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the attached claims.

Claims

1. A high-toughness polyolefin film, wherein the high-toughness polyolefin film is obtained by melt extrusion and stretching of polyolefin film material pellets composed of a first polymer component, a second polymer component, and an auxiliary material component, wherein: In parts by mass, the content of the first polymer component is 100 parts; the content of the second polymer component is 1-15 parts; In parts by mass, the auxiliary material components include 0-0.5 parts of antioxidant, 0-0.5 parts of compatibilizer, 0.5-2.5 parts of cross-linking agent, 0-0.2 parts of auxiliary cross-linking agent and 0-0.2 parts of anti-blocking agent; The first polymer component is a copolymer of ethylene or propylene and three different α-olefins, wherein the α-olefin is selected from α-olefins having more than 3 carbon atoms and less than 12 carbon atoms, and the content of the ternary segment structure I composed of three consecutive α-olefin units in the first polymer component is 0.001 mol%-3 mol%; the three α-olefins are α-olefin A, α-olefin B, and α-olefin C in order of carbon atom number from small to large, and in the first polymer component, the molar ratio of α-olefin A, α-olefin B, and α-olefin C is (0.1-2.5):1:(0.1-4.0); The second polymer component is one or more of low-density polyethylene (LDPE), polybutene-1 (PB-1), ethylene-vinyl acetate copolymer (EVA), olefin multi-block copolymer (OBC), ethylene propylene diene monomer rubber (EPDM) or thermoplastic polyurethane elastomer (TPU).

2. The high-toughness polyolefin film according to claim 1, characterized in that: The first polymer component has a weight average molecular weight of 3-400 kg / mol, a molecular weight distribution index of 1.1-5.0, a melting temperature of 30-110°C, a tensile strength of 1-30 MPa, no fracture in an impact test at room temperature and -20°C, and a Shore A hardness of 45-90.

3. The high-toughness polyolefin film according to claim 1, characterized in that: The combination of three different α-olefins in the first polymer component is 1-butene / 1-pentene / 1-hexene, 1-butene / 1-pentene / 1-heptene, 1-butene / 1-pentene / 1-octene, 1-butene / 1-pentene / 1-nonene, 1-butene / 1-hexene / 1-heptene, 1-butene / 1-hexene / 1-octene, 1-butene / 1-hexene / 1-nonene, 1-butene / 1-heptene / 1-octene, 1-butene / 1-hexene / 1-nonene, 1-butene / 1-heptene / 1-octene, 1-butene / 1-heptene / 1-octene, 1-butene / 1-hexene / 1-nonene, 1-butene / 1-heptene / 1-octene, 1-butene / 1-hexene / 1-heptene / 1-octene, 1-butene / 1-hexene / 1-nonene, 1-butene / 1-heptene / 1-octene, 1-butene / 1-pent ... One of 1-heptene / 1-nonene, 1-pentene / 1-hexene / 1-heptene, 1-pentene / 1-hexene / 1-octene, 1-pentene / 1-hexene / 1-nonene, 1-pentene / 1-heptene / 1-octene, 1-pentene / 1-heptene / 1-nonene, 1-pentene / 1-heptene / 1-octene, 1-pentene / 1-heptene / 1-nonene, 1-pentene / 1-octene / 1-nonene, 1-hexene / 1-heptene / 1-octene, 1-hexene / 1-heptene / 1-nonene, 1-heptene / 1-octene / 1-nonene.

4. The high-toughness polyolefin film according to claim 1, characterized in that: The molar ratio of α-olefin A, α-olefin B and α-olefin C in the first polymer component is (0.3-2.5):1:(0.3-2.5), and the molar ratio of α-olefin to ethylene or propylene is (0.1-1.0):

1.

5. The high-toughness polyolefin film according to claim 1, characterized in that: In the first polymer component, the content of ternary segment structure II consisting of two continuous α-olefin units and one ethylene unit is 0.01 mol%-15 mol%, the content of ternary segment structure III consisting of two discontinuous α-olefin units and one ethylene unit is 0.01 mol%-15 mol%, and the content of ternary segment structure IV consisting of three continuous ethylene units is 50 mol%-90 mol%.

6. The high-toughness polyolefin film according to claim 1, characterized in that: The first polymer component is prepared by a high-temperature solution polymerization process, wherein the temperature of the solution polymerization process is 100-180° C. and the pressure is 10-50 bar. The catalyst is selected from one or more of a metallocene catalyst, a late transition metal catalyst, a Ziegler-Natta catalyst, a non-metallocene catalyst, and a FI catalyst. The co-catalyst is selected from one or more of methylaluminoxane, modified methylaluminoxane, ethylaluminoxane, butylaluminoxane, trimethylaluminum, triethylaluminum, triisobutylaluminum, trihexylaluminum, trioctylaluminum, diethylaluminum monochloride, ethylaluminum dichloride, triphenylborane, tri(4-fluorophenyl)borane, tri(pentafluorophenyl)borane, tri(3,5-difluorophenyl)borane, and tri(2,4,6-trifluorophenyl)borane.

7. A method for preparing the high-toughness polyolefin film according to any one of claims 1 to 6, characterized in that: The first polymer component, the second polymer component and the auxiliary material component in the formula amount are mixed by a high-speed mixer at a speed of 100-1000 rpm for 10-30 min, and then melt-extruded by a twin-screw extruder, pelletized and dried to obtain high-toughness polyolefin film pellets; the high-toughness polyolefin film pellets are melt-extruded by a single-screw extruder, and stretched at a stretching ratio of 2-20 times to obtain a film with a thickness of 2-700 μ m high toughness polyolefin film.

8. The method for preparing a high-toughness polyolefin film according to claim 7, characterized in that: The temperature of the twin-screw extruder is 60-230°C and the rotation speed is 10-200 rpm.

9. The method for preparing a high-toughness polyolefin film according to claim 7, characterized in that: The temperature of the single screw extruder is 70-200°C, the speed is 10-200 rpm, the stretching ratio is 3-15 times, and the thickness of the high-toughness polyolefin film is 2-600 μ m.

10. Use of the high-toughness polyolefin film according to any one of claims 1 to 7 in the preparation of packaging films, sealing components, heavy packaging films, and POF films for crystalline silicon cells, perovskite cells, and organic thin-film cells.

Citation Information

Patent Citations

  • Polyolefin film and application thereof

    CN106893183A

  • A polyolefin film, its preparation method, and a photosensitive material capping film containing the same.

    CN108177401B

  • Ethylene-based polymer compositions, methods of making the same, and articles prepared therefrom

    CN101688032A

  • Multilayer heat-shrinkable film

    CN106585018A